ANALISIS BULLWHIP EFFECT DAN E-COMMERCE DALAM SISTEM RANTAI PASOK PRODUK MAKANAN - Djamal, Nugraheni; Winarno, Heru; Jihan Shofa, Mohamad; Sah Putra, Al Fiillian (LPPM Universitas Sangga Buana, 2024)
The purpose of this study is to measure the value of the bullwhip effect, identify its causes, and find solutions to reduce it. The problem of the bullwhip effect, where their order fluctuations exceed demand fluctuations, resulting in raw material shortages and production stops. This study examines two echelons in the supply chain and uses the FMEA method. The results showed that the bullwhip effect value at echelon 1 (supplier and PPIC) was 1.66, while at echelon 2 (PPIC and Customer) was 0.63. This indicates the presence of a bullwhip effect at echelon 1, while echelon 2 is not affected. Some of the main causes of the bullwhip effect include raw material procurement not meeting orders, material price increases, uncertainty in demand information, large raw material orders and sales volumes greater than raw material receipts. solutions that can be done between suppliers need to implement an information system using E-commerce such as shopee in order to further expand the marketing network and facilitate product distribution to consumers so that online ordering